The Influence Of Teaching Style And Flexibility On Kayang Learning Outcomes - Hidasari, Fitriana Puspa; Bafadal, Muhammad Fachrurrozi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2020)
The purpose of this study was to see how much difference the impact of the two teaching styles, flexibility on learning kayang. The sample was students of SMP 6 Pontianak City, totaling 48 students, which were divided into 4 groups, with details consisting of 12 students per group. Quantitative method which has the form of Experiment with FACTORIAL design by level 2 x 2 is a research method. Two-way analysis of variance is a way of analyzing in this study, followed by a normality test and a homegeneity test. After that, the Tukey test was continued with a significance level of ? = 0.05. This research has succeeded in answering several hypotheses that have been proposed. The first is the Inclusive Teaching Style (GMI) has a significant effect compared to the Exercise Teaching Style (GML) on kayang learning outcomes. The second is that GMI and GML have a strong interaction with the rich learning outcomes. The third is that GMI is more appropriate to be applied than GML for students who have high flexibility in the learning outcomes of kayang. The fourth is that GML is more appropriately applied compared to GMI in students who have low flexibility in the learning outcomes of kayang.